2019
DOI: 10.7554/elife.39495
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide B mediates female sexual receptivity in medaka fish, acting in a female-specific but reversible manner

Abstract: Male and female animals display innate sex-specific mating behaviors. In teleost fish, altering the adult sex steroid milieu can effectively reverse sex-typical mating behaviors, suggesting remarkable sexual lability of their brains as adults. In the teleost medaka, neuropeptide B (NPB) is expressed female-specifically in the brain nuclei implicated in mating behavior. Here, we demonstrate that NPB is a direct mediator of estrogen action on female mating behavior, acting in a female-specific but reversible man… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 71 publications
2
41
0
Order By: Relevance
“…In particular, contrary to males, mutant females showed highly significant upregulation of Neuropeptide-like precursor 4 (nplp4) and target of brain insulin (tobi) genes (p = 5 × 10 −5 ). Neuropeptides and insulin signaling have been implicated in multiple aspects of sex-specific behavior and physiology including mating and reproduction 23,24 , and, as our data indicate, brain-expressed Tud may partially contribute to these processes in Drosophila. Interestingly, a recent study also showed the upregulation of tobi in the fly heads in response to the accumulation of β-amyloid peptide (Aβ) in the Alzheimer's disease Drosophila model 25 .…”
Section: Resultssupporting
confidence: 51%
“…In particular, contrary to males, mutant females showed highly significant upregulation of Neuropeptide-like precursor 4 (nplp4) and target of brain insulin (tobi) genes (p = 5 × 10 −5 ). Neuropeptides and insulin signaling have been implicated in multiple aspects of sex-specific behavior and physiology including mating and reproduction 23,24 , and, as our data indicate, brain-expressed Tud may partially contribute to these processes in Drosophila. Interestingly, a recent study also showed the upregulation of tobi in the fly heads in response to the accumulation of β-amyloid peptide (Aβ) in the Alzheimer's disease Drosophila model 25 .…”
Section: Resultssupporting
confidence: 51%
“…Moreover, recent studies have revealed that expression of NPB by, yet, not identified types of neurons in the Japanese rice fish (Medaka) is female-specific, i.e. is mediated only by binding of ovarian sex hormones (estrogens) to receptors of the androgen/estrogen signaling cascade (52: Hiraki-Kajiyama et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The mating behavior test was performed essentially as described elsewhere ( Hiraki-Kajiyama et al, 2019 ). In brief, on the day before behavioral testing, each focal male and female (from Δ2 and Δ10 knockout lines) was placed with a stimulus fish of the opposite sex (wild-type d-rR strain) in a 2-l rectangular tank, separated by a perforated transparent partition.…”
Section: Methodsmentioning
confidence: 99%
“…A rabbit anti-GAL antibody that recognizes teleost Gal with high specificity ( Rodríguez et al, 2003 ; Amano et al, 2009 ) was obtained from Enzo Life Sciences (Farmingdale, NY; RRID: AB_2051473 ). The specificity of this antibody was confirmed in medaka brain by a double-labeling experiment using immunohistochemistry and in situ hybridization, essentially as described elsewhere ( Hiraki-Kajiyama et al, 2019 ) with slight modifications. In brief, frozen coronal brain sections of 20 μm thickness were cut as described above and hybridized with the above-mentioned gal probe, which was labeled with fluorescein by using Fluorescein RNA Labeling Mix and T7 RNA polymerase (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation